Glutathione Activates Type III Secretion System Through Vfr in Pseudomonas aeruginosa - Zhang, Yani; Zhang, Chao; Du, Xiao; Zhou, Yun; Kong, Weina; Lau, Gee W.; Chen, Gukui; Kohli, Gurjeet Singh; Yang, Liang; Wang, Tietao; Liang, Haihua (Frontiers in Cellular and Infection Microbiology, 2019)
Glutathione (GSH) is the most abundant antioxidant in all living organisms. Previously, we have shown that a deletion mutant in the glutathione synthetase gene (ΔgshB) decreases the expression of type III secretion system (T3SS) genes of Pseudomonas aeruginosa. However, the mechanism remains elusive. In this study, a comprehensive transcriptomic analysis of the GSH-deficient mutant ΔgshAΔgshB was used to elucidate the role of GSH in the pathogenesis of P. aeruginosa. The data show that the expression of genes in T3SS, type VI secretion system (T6SS) and some regulatory genes were impaired. ΔgshAΔgshB was attenuated in a mouse model of acute pneumonia, swimming and swarming motilities, and biofilm formation. Under T3SS inducing conditions, GSH enhanced the expression of T3SS in both wild-type PAO1 and ΔgshAΔgshB, but not in Δvfr. Genetic complementation of Δvfr restored the ability of GSH to induce the expression of T3SS genes. Site-directed mutagenesis based substitution of cysteine residues with alanine in Vfr protein abolished the induction of T3SS genes by GSH, confirming that GSH regulates T3SS genes through Vfr. Exposure to H2O2 decreased free thiol content on Vfr, indicating that the protein was sensitive to redox modification. Importantly, GSH restored the oxidized Vfr to reduced state. Collectively, these results suggest that GSH serves as an intracellular redox signal sensed by Vfr to upregulate T3SS expression in P. aeruginosa. Our work provides new insights into the role of GSH in P. aeruginosa pathogenesis.